Development of Teaching Material to Support Merdeka Curriculum on the Acid-Base of Phase F - Rahmi Fadila; Mawardi Mawardi; Okta Suryani (Edunesia: Jurnal Ilmiah Pendidikan, 2023)
This research aims to develop teaching materials to support Merdeka curriculum learning on acid-base phase F SMA/MA material that is valid and practical. This educational development research uses the Plomp model developed by Tjeerd Plomp. The development procedure includes the initial investigation and development or prototyping stages. The subjects in this study were UNP chemistry lecturers, SMA Negeri 2 Padang teachers, and Phase F students of SMA Negeri 2 Padang. The research instruments used validation sheets and teacher and learner response questionnaires. The results of this study indicate that teaching materials to support Merdeka curriculum learning on acid-base phase F SMA / MA material that has been developed and assessed by five expert validators are on valid criteria with an average of 0.86, an efficient category in teacher responses by obtaining a percentage of 87%, and student responses by obtaining a percentage of 97%. This teaching material is proven to increase students' learning motivation and understanding, as well as facilitate teachers and students in the learning process of the Merdeka curriculum.